Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"--Page 4 de la couverture.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

Nous sommes le produit d’un contexte - O'Leary, Véronique; St-Pierre, Josée.; Toupin, Louise (Québécoises deboutte! Tome 1. Une Anthologie de textes du Front de libération des femmes (1969-1971) et du Centre des femmes (1972-1975)., 1983)
Le volume 1 (212 p.) comprend des tracts, documents internes, manifestes et lettres diffusées par les deux groupes entre 1969 et 1975, de même qu'un aperçu de la couverture de presse dont ils bénéficièrent à l'époque. Le volume 2 (377 p.) reprend la collection complète du journal ##Québécoises deboutte## publié entre 1972 et 1975, par le Centre des femmes; on y a ajouté des tables rondes.
Keywords: 1900-1999; 1960-1969; 1970-1979; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; histoire et politique; inégalités; militance; postmodernisme; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques